Łączenie historią. Dzieje miasta i gminy na łamach "Łącznika Zielonogórskiego" = Combining history. The history of the town and the municipality in "Łącznik Zielonogórski" - Korniluk, Izabela (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This article presents historical subjects discussed in "Łącznik Zielonogórski", a new journal published since October 2012. Its main purpose was to inform the inhabitants of Zielona Góra and the neighboring villages about the planned merger of the two administrative units. Tomasz Czyżniewski, the editor-in-chief of the magazine , began a series of historical articles under the common title "Zielona Góra Walk" on the last page of the magazine, taking up many threads from the history of Zielona Góra and the villages which were to become a part of the New Town from 2015. The intention of the editor T. Czyżniewski was to include the history of the two administrative units in the newspaper, which was supposed to inform the public about the integration processes of the city with the municipality, and thus to show that the history of the municipality and the history of town are connected. Although the city and the neighbouring villages, so far, were governed by their own rules, both local governments had one thing in common - their history. And if it was not possible to find a common element, then the journalist intended to present historical information about every village, community or gathering in such a way as to interest the readers and inhabitants of both administrative units, and make them see it as unusual. The journalist, through his essays, shows a lot of inventiveness in popularizing historical knowledge about the past of not only Zielona Góra, but also its immediate vicinity. It is important to appreciate the "Łącznik" and its cycle of articles, but also to present the phenomenon of increased interest in local history. One of the many merits of the "Łącznik Zielonogórski " is making the town inhabitants open not only to the history of Zielona Góra itself, but above all, to the history of villages contained now within an enlarged town. The knowledge of the colourful history of individual villages was known, previously, only to their residents or even just enthusiasts. Now it enriches the knowledge of all citizens, taking away the anonymity of individual villages.
Keywords: czasopisma; czasopisma lokalne; Czyżniewski, Tomasz; Łącznik Zielonogórski (czasopismo); magazines; local magazines